MANAGEMENT OF ARDS IN DROWNING PATIENT IN INTENSIVE CARE UNIT - Susilo, Heru; Yun Jufan, Akhmad (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Acute Respiratory Distress Syndrome (ARDS) occured in drowning patients in both fresh or salt water. This is a consequence of aspiration of fluid into the lungs. This condition can be made worse by the possibility of hypothermia, arrhythmia, or neurological impacts as a result of anoxia. A male, 16 years old, 60 kg without comorbid was drowned in a well, came on referral from a another hospital, he was admitted to the ward for 2 days. The patient arrived in emergency room and the patient is in respiratory failure state and ARDS. This patient was given intubation in the emergency room, after this patient is stable he was transfered to ICU. In the ICU, the patient was given mechanical ventilation therapy on 4th day and then he was given weaning gradually, on 7th day the patient was given extubation. In general, treatment outcome of drowned patient really depends on how effective and fast the maangement of the respiratory distress in the incident location and until taken to hospital. Mechanical ventilation therapy follows the general ARDS management pattern, using PEEP and lung protection strategies. Monitoring and caution is needed during the weaning process to prevent recurrence of pulmonary edema and re-intubation.